2016
DOI: 10.3390/diseases5010001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamics in Mitochondrial Diseases

Abstract: Mitochondria are very versatile organelles in continuous fusion and fission processes in response to various cellular signals. Mitochondrial dynamics, including mitochondrial fission/fusion, movements and turnover, are essential for the mitochondrial network quality control. Alterations in mitochondrial dynamics can cause neuropathies such as Charcot-Marie-Tooth disease in which mitochondrial fusion and transport are impaired, or dominant optic atrophy which is caused by a reduced mitochondrial fusion. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 112 publications
(134 reference statements)
2
99
0
Order By: Relevance
“…The molecular machinery that mediates this organelle fission and fusion is thus necessary to maintain MT integrity and is tightly regulated by post-translational modifications and protein-protein interactions [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular machinery that mediates this organelle fission and fusion is thus necessary to maintain MT integrity and is tightly regulated by post-translational modifications and protein-protein interactions [2].…”
Section: Introductionmentioning
confidence: 99%
“…A defective mitochondrial dynamic machinery could have important physiological consequences including embryonic lethality and diseases [2] (Table 1), suggesting that fission and fusion go far beyond the morphological aspect of mitochondria. Mitochondrial dynamics have been linked to multiple mitochondrial functions.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal circumstances, fusion and fission occur simultaneously and at approximately the same rate; accordingly, any change in the homeostatic balance due to cellular stimuli may result in elongated or fragmented mitochondria. The physiological significance of mitochondrial fusion and/or fission dysfunction is illustrated by the growing number of pathological conditions related directly to mitochondrial homeostasis (Table ) …”
Section: Mitochondrial Homeostasismentioning
confidence: 99%
“…The physiological significance of mitochondrial fusion and/or fission dysfunction is illustrated by the growing number of pathological conditions related directly to mitochondrial homeostasis (Table 1). 17,18…”
Section: Under Normal Circumstances Fusion and Fission Occur Simultamentioning
confidence: 99%
“…Progress in mitochondrial research has shown that mitochondria are versatile and dynamic organelles that can undergo fusion, fission, biogenesis and autophagic elimination to maintain mitochondrial network quality control in response to various cellular signals (Suárez‐Rivero et al, ). One important breakthrough in the field of Mitochondrial Research was the delineation of how mitochondrial dynamics is linked to bioenergetics and signaling functions of the organelle.…”
Section: Mitomeeting Opening Lectures: “Leopoldo Demeis Conference”mentioning
confidence: 99%